Moving Toward a More Comprehensive Analysis of Acceleration Profiles in Elite Youth Football - Kovacevic, Damian; Elias, George; Ellens, Susanne; Cox, Adam; Serpiello, Fabio R. (Frontiers in Sports and Active Living, 2022)
In football, having greater acceleration ability may decide the most important moments within matches. Up to now, commonly used acceleration variables have typically been investigated in isolation, with each variable suffering from unique limitations. Subsequently, any findings may provide a limited representation of what specific acceleration demands had actually occurred. Without gaining a comprehensive understanding of acceleration demands in football, it appears difficult to identify how to best monitor and maximise the long-term development of acceleration ability in footballers, all whilst doing so in a safe, sport-specific manner. Moving towards a comprehensive analysis of acceleration profiles addresses this, as it can provide a more robust, informative understanding of the unique acceleration demands of competitive match-play. This perspective article aims to discuss the benefits of adopting a comprehensive analysis of the acceleration demands during competitive matches for football players, by simultaneously analysing high-intensity accelerations, repeated high acceleration ability (RHAA), and average acceleration. We discuss examples of the calculation and application of comprehensive acceleration profiles at a team level throughout the course of an entire elite youth football season, as well as on an individual level. Monitoring acceleration profiles comprehensively not only appears important from a training load/injury prevention perspective, but also, equips coaches and conditioning staff with the specific information necessary to develop and prescribe individualised, acceleration-emphasised training protocols that are replicable to the demands of match-play. Examples of such protocols are provided.